Humeral Fracture in a Young CrossFit Practitioner - Costa, Diogo (2023)
CrossFit (CrossFit Inc, Washington, DC) is a recent, high-intensity strength and conditioning sport that is growing in popularity worldwide. Potential risks and injuries have been described in previous reports. Distal humeral fractures without direct trauma were related to sports like baseball or wrestling. However, they have never been reported in a CrossFit athlete. We present the first case of distal humeral fracture associated with a CrossFit workout, during a gymnastic movement. Our patient had no relevant medical history but the investigation revealed reduced vitamin D levels and low bone density. The patient was surgically treated and he completed the rehabilitation program. He returned to sports practice 12 weeks after the surgery